2018
DOI: 10.1177/2055668318790650
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a microprocessor-controlled hydraulic ankle on the kinetic symmetry of trans-tibial amputees during ramp walking: A case series

Abstract: Introduction Asymmetrical limb loading is believed to cause health problems for lower limb amputees and is exacerbated when walking on slopes. Hydraulically damped ankle-feet improve ground compliance on slopes compared to conventional prosthetic feet. Microprocessor-controlled hydraulic ankle-feet provide further adaptation by dynamically adjusting viscoelastic damping properties. Method Using a case series design, gait analysis was performed with four trans-tibial amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The PwrAF surveyed in this study has a plantarflexion range of motion of 22° that is not only used for powered push-off but also passively for foot-flat during level walking and terrain adaptation. Descending a slope or negotiating uneven terrain with a passive microprocessor-controlled prosthetic ankle resulted in reduced (more normal) early stance knee flexion, slowed (better passively controlled) forward shank rotation, reduced negative (dampening) work in the residual knee, and thus, improved control over downhill walking speed as compared with a foot with fixed ankle attachment 59 . Therefore, even passive adaptation of microprocessor-controlled ankles significantly reduced biomechanical compensations and residual knee loading during slope descent and uneven terrain ambulation, both on the sound and amputated side 59,60 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PwrAF surveyed in this study has a plantarflexion range of motion of 22° that is not only used for powered push-off but also passively for foot-flat during level walking and terrain adaptation. Descending a slope or negotiating uneven terrain with a passive microprocessor-controlled prosthetic ankle resulted in reduced (more normal) early stance knee flexion, slowed (better passively controlled) forward shank rotation, reduced negative (dampening) work in the residual knee, and thus, improved control over downhill walking speed as compared with a foot with fixed ankle attachment 59 . Therefore, even passive adaptation of microprocessor-controlled ankles significantly reduced biomechanical compensations and residual knee loading during slope descent and uneven terrain ambulation, both on the sound and amputated side 59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…Descending a slope or negotiating uneven terrain with a passive microprocessor-controlled prosthetic ankle resulted in reduced (more normal) early stance knee flexion, slowed (better passively controlled) forward shank rotation, reduced negative (dampening) work in the residual knee, and thus, improved control over downhill walking speed as compared with a foot with fixed ankle attachment. 59 Therefore, even passive adaptation of microprocessor-controlled ankles significantly reduced biomechanical compensations and residual knee loading during slope descent and uneven terrain ambulation, both on the sound and amputated side. 59,60 These results may also be assumed for the PwrAF, which may explain the reduction in amputated side knee pain found by the PwrAF.…”
Section: Potential Mechanisms For the Reduction In Amputated Side Kne...mentioning
confidence: 99%
See 1 more Smart Citation
“…All these effects of a prosthetic ankle joint result in decreased loading of the residual knee (46). In addition, the adaptability of the prosthetic ankle on slopes and uneven terrain reduces biomechanical compensations on the prosthetic and sound limbs, facilitates faster foot-flat, improves the control of downhill walking speed, and significantly reduces the biomechanical loading of the residual knee (47)(48)(49)(50). These effects that have been shown for passive feet with non-microprocessor and microprocessor-controlled ankles may also be assumed for the powered ankle-foot components surveyed and may explain the reduction in amputated side knee pain.…”
Section: Biomechanical Mechanisms For Unloading Of the Amputated Side...mentioning
confidence: 99%
“…With focusing on commercially available MPF without powered ankle support, previous studies on slope ambulation have shown mixed results with improvements in some biomechanical parameters but deterioration in others [ 21 ], further complicated by high inter-subject variability [ 13 ]. Many of these studies were limited by the only gradual and partial adaptation of the studied MPF to slopes [ 13 , 21 ] or testing on only shallow slopes of 5° of a MPF with very limited ROM at the ankle joint [ 11 , 18 , 22 ]. Moreover, the vast majority of studies investigated slope ambulation with MPF only for persons with TTA.…”
Section: Introductionmentioning
confidence: 99%